Restoration of impaired ecosystems: An ounce of prevention or a pound of cure? Introduction, overview, and key messages from a SETAC‐SER workshop. (28th September 2015) - Farag, Aïda M; Hull, Ruth N; Clements, Will H; Glomb, Steve; Larson, Diane L; Stahl, Ralph; Stauber, Jenny
ABSTRACT: A workshop on Restoration of Impaired Ecosystems was held in Jackson, Wyoming, in June 2014. Experts from Australia, Canada, Mexico, the United Kingdom, and the United States in ecotoxicology, restoration, and related fields from both the Society of Environmental Toxicology and Chemistry and the Society for Ecological Restoration convened to advance the practice of restoring ecosystems that have been contaminated or impaired from industrial activities. The overall goal of this workshop was to provide a forum for ecotoxicologists and restoration ecologists to define the best scientific practices to achieve ecological restoration while addressing contaminant concerns. To meet this goal, participants addressed 5 areas: 1) links between ecological risk assessment and ecological restoration, 2) restoration goals, 3) restoration design, 4) monitoring for restoration effectiveness and 5) recognizing opportunities and challenges. Definitions are provided to establish a common language across the varied disciplines. The current practice for addressing restoration of impaired ecosystems tends to be done sequentially to remediate contaminants, then to restore ecological structure and function. A better approach would anticipate or plan for restoration throughout the process. By bringing goals to the forefront, we may avoid intrusive remediation activities that close off options for the desired restoration. Participants realized that perceived limitations in the site assessment process hinder consideration of restoration goals; contaminant presence will influence restoration goal choices; social, economic, and cultural concerns can factor into goal setting; restoration options and design should be considered early during site assessment and management; restoration of both structure and function is encouraged; creative solutions can overcome limitations; a regional focus is imperative; monitoring must occur throughout the restoration process; and reciprocal transfer of knowledge is needed among theorists, practitioners, and stakeholders and among varied disciplines. Integr Environ Assess Manag 2016;12:247–252. © 2015 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of SETAC Key Points: This work summarizes key messages from a workshop supported by SETAC and the Society of Ecological Restoration. Restoration of contaminated sites has traditionally been a compartmentalized and sequential process, we propose a shift to a restoration continuum. This continuum involves more reciprocal transfer of knowledge among varied disciplines, bringing restoration planning and goals to the forefront during assessments and remediation, conducting monitoring throughout the process, and taking a more regional focus during the restoration. Social, economic and cultural concerns must be factored in to the restoration goalsetting process and unique goals may be needed for contaminated ecosystems.